Financial inclusion in female entrepreneurship in Peru: A systematic review - Luis Enrique Dios Zárate,; Luis Miguel Romero Echevarria,; Juan Francisco Vento Rojas,; Marlene Cusi Montesinos,; Korina Asqui Gomez, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Financial inclusion influences entrepreneurship led by women, emerging as a key aspect in the economic growth of a country. The study was based on pure research, qualitative approach, systematic review and Preferred Reporting Items for Systematic Reviews and Meta-Analyses (Prisma) statement. The investigation explained that financial inclusion has had an impact on female entrepreneurship, however, there are gaps, as well as financial barriers that impede the economic development of women, in addition to increasing their probability of starting a business. In this way, it was concluded that financial inclusion is crucial for women entrepreneurs; however, there are still difficulties in accessing adequate tools and financing, emphasizing the need for regulations that promote gender equality and guarantee the success of the projects. women-led ventures